RANCANG BANGUN PENERANGAN DENGAN SUMBER DARI PHOTOVOLTAIC DENGAN MEMANFAATKAN RANGKAIAN BOOSTER - Amin, Muhammad; Ananda, Ricki (Riau Journal Of Computer Science, 2018)
Basic Electricity or TDL tariffs are currently increasing, as evidenced by the absence of 450 Watt power supplied by PLN (State electricity company) and the increasing power consumption pertiap year. Lighting is one of the TDL parts, so nowadays to reduce the consumption of TDL from lighting many different ways used such as making energy-saving lamps from the led diodes, up to the use of solar panels as a lighting supply to minimize the use of TDL.Didasari from it, then this study discusses the design of illumination with the source of photovoltaic (solar panel), by pressing the cost of the battery minimize, so used ripab boster. From the test results obtained, the system designed to be felt quite efficient, due to the input 3.7 V and 12 Watt load can increase the voltage of 38.7 V. In addition, the combined LDR switch system on the booster is also able to work on efficient heat, so on the 0-5cm test from the ldr sensor to the light, the switch system of the 3D FIR still remains active, up to a distance of 10- 15 from the ldr light sensor, the switch system is off. With the schedule of charging from USB TP4056, at 07.00-08.00 obtained the results of light emitted USB of 1.6 V to charge the battery, and on the hour perceived a fairly efficient pengasan, because the sunlight is quite hot, so that at 11:00 to 12:00 the usb output voltage is 2.2 V.